Methicillin-Resistant Staphylococcus aureus-Induced Discitis Following Acupuncture: A Case Report - Yang W; Xia S; Li L; Xu J; Ji H; Yao W; Shi F (Infection and Drug Resistance)
Weihang Yang,1,* Shuang Xia,1,* Liang Li,1,* Jiahao Xu,1,* Hongjian Ji,2,* Wanglin Yao,1 Fengchao Shi1 1Department of Orthopedics, Affiliated Hospital 6 of Nantong University, The Third People’s Hospital of Yancheng, Yancheng, Jiangsu, People’s Republic of China; 2Department of Pharmacy, Jiangsu Vocational College of Medicine, College of Pharmacy, Yancheng, Jiangsu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Fengchao Shi; Wanglin Yao, Department of Orthopaedics, Affiliated Hospital 6 of Nantong University, The Third People’s Hospital of Yancheng, Yancheng, Jiangsu, 224000, People’s Republic of China, Tel +86-15189200280 ; +86-15995185295, Email shifengchao1980@126.com; 575733189@qq.comAbstract: This report describes a case of lumbar disc infection potentially induced by acupuncture in a 43-year-old male with a history of back pain. After acupuncture treatment at another hospital, the patient experienced worsened pain. Physical examination revealed tenderness at the upper lumbar intervertebral space and paravertebral percussion pain. Laboratory tests showed no bacterial growth in both aerobic and anaerobic blood cultures after 5 days, but C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR) were significantly elevated. CT and MRI scans revealed osteolysis of the L2/3 vertebral body and a paraspinal abscess in the left psoas muscle. The patient was treated with intravenous vancomycin (1 g every 12 hours for 4 weeks). After two weeks, CRP normalized, but ESR remained elevated. By week three, CRP increased to 61.19 mg/L, and severe anemia developed. Follow-up MRI indicated worsening of the lumbar infection. A transfusion was performed, and surgery was conducted in the fourth week. Intraoperative findings confirmed methicillin-resistant Staphylococcus aureus (MRSA) as the causative pathogen. Postoperatively, symptoms improved, and inflammatory markers normalized. This case highlights the need for standardized acupuncture practices and prompt surgical intervention in cases of infectious discitis unresponsive to conservative treatment.Keywords: acupuncture, lumbar discitis, methicillin-resistant Staphylococcus aureus, surgical treatment